Armenia : Restructuring to Sustain Universal General Education - Perkins, Gillian (Washington, DC: World Bank, 2013)
Before the breakup of the Soviet Union, Armenia had a highly developed and expensive education system, matching the needs of the command economy. The country is now facing a challenge to sustain universal coverage and performance standards in primary-secondary education with a small fraction of the former budget, while reorienting the system to the needs of a democratic society and market economy. The purposes of this paper are to clarify the case for rationalization by quantifying the future cost implications and affordability of various educational policy options, and to identify further measures needed in Armenia to promote restructuring and to secure adequate financing of the education system over the medium term. The paper examines recent evolution of the structure of inputs and expenditure to general education in Armenia in comparison with international norms and practice, and outlines various approaches that have been proposed for restructuring the system in the context of the government's sectoral reform strategy. Conclusions are drawn concerning the depth of rationalization and the financing strategy that would be needed to sustain universal access and quality of the system over the medium term. Finally, some of the practical and institutional obstacles to actually implementing rationalization are identified, and measures are proposed to help overcome these constraints.